Remnant Pancreatectomy for Recurrent or Metachronous Pancreatic Carcinoma Detected by FDG-PET: Two Case Reports - Koizumi, Masaru; Sata, Naohiro; Kasahara, Naoya; Morishima, Kazue; Sasanuma, Hideki; Sakuma, Yasunaru; Shimizu, Atsushi; Hyodo, Masanobu; Yasuda, Yoshikazu (JOP. Journal of the Pancreas, 2016)
Context Although surgical resection is the only curative therapeutic option for recurrent or metachronous pancreatic carcinomas, most such cancers are beyond surgical curability. We herein report on two rare cases of remnant pancreatectomy used to treat recurrent or metachronous pancreatic carcinomas. Case reports Case#1 A 65-year-old male developed weight loss and diabetes mellitus 83 months after a pylorus-preserving pancreaticoduodenectomy followed by two years of adjuvant chemotherapy (5-fluorouracil plus leucovorin plus mitomycin C) for a pancreatic carcinoma in the head of the pancreas (stage IA). An abdominal CT scan revealed a 3 cm tumor in the remnant pancreas which appeared as a ‘hot’ nodule on FDG-PET. A remnant distal pancreatectomy was performed and a pancreatic carcinoma similar in profile to the primary lesion (stage IIB) was confirmed pathologically. Case#2 A 67-year-old male showed increased CA 19-9 levels 25 months after a distal pancreatectomy for a pancreatic carcinoma in the body of the pancreas (stage IA). An abdominal CT scan revealed a cystic lesion in the cut end of the pancreas which appeared as a ‘hot’ nodule on FDG-PET. A remnant proximal pancreatectomy with duodenectomy was performed and a metachronous pancreatic carcinoma (stage III) was confirmed pathologically. Conclusion Remnant pancreatectomy can be considered a treatment option for recurrent or metachronous pancreatic carcinomas. FDG-PET can play a key role in detecting remnant pancreatic carcinomas. Image: FDG-PET showing a hot spot at the cut end of the pancreatic head.